2008
DOI: 10.1038/labinvest.2008.92
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of the NADPH oxidase subunit p47phox on vascular TLR expression and neointimal lesion formation in high-fat diet-induced obesity

Abstract: Reactive oxygen species (ROS) formation is associated with inflammation and vasculature dysfunction. We investigated the potential role of the NADPH oxidase on vascular Toll-like receptor (TLR) expression and carotid neointimal formation in high-fat (HF) diet-induced obesity (DIO) model. Using mice DIO and common carotid artery flow cessation-induced lesion formation models, we examined vascular TLR2 and TLR4 expression and neointimal formation in NADPH oxidase subunit p47 phox -deficient (p47 phox-/-) mice. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 50 publications
3
33
0
Order By: Relevance
“…This was also confirmed with knockout of the p47 phox subunit of NADPH oxidase (7). NADPH oxidase composed of p22 phox , p47 phox , and p67 phox plays a crucial role in the generation of ROS and hence serves a potential role in providing a host defense.…”
Section: Discussionmentioning
confidence: 58%
“…This was also confirmed with knockout of the p47 phox subunit of NADPH oxidase (7). NADPH oxidase composed of p22 phox , p47 phox , and p67 phox plays a crucial role in the generation of ROS and hence serves a potential role in providing a host defense.…”
Section: Discussionmentioning
confidence: 58%
“…Similarly, leptin at a low dose is unable to modify endothelial progenitor cell migration in response to a scratch wound [46], although at a high dose it is able to reduce the migration of these cells. However, the specific role of leptin on endothelial cell migration seems unclear because some studies have reported that this factor can act as a chemoattractive factor in endothelial cells [40,47]. …”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: 25-HC, 25-hydroxycholesterol; HMG CoA reductase, 3-hydroxy-3-methylglutaryl CoA reductase; AUC, areas under curves; cPKC, conventional proteinkinase C; ERK, extracellular signal-regulated kinase; HBSS, Hanks balanced salt solution; HC, hypercholesterolemia; JAK/STAT, janus kinase/signal transducer and activator of transcription; MAPK, mitogen activated proteinkinase; OW monocytes, monocytes derived from overweight patients; NFB, nuclear factor B; PTX, pertussis toxin; PMA, phorbol 12-myristate 13-acetate; PI3K, phosphatidilinositol 3 kinase; SREBP2, sterol regulatory element-binding protein2; SCAP, SREBP cleavageactivating protein; SOCS, suppressor of cytokine signaling; WMN, wortmannin. Through these signal pathways leptin exerts many physiological and pathological effects on its target-cells, both by directly modifying protein function in the cytoplasm and through gene expression regulation in the nucleus (Dong et al 2006;Chen and Stinnett 2008). We found a concentration-dependent biphasic effect of leptin on cholesterol biosynthesis of control monocytes.…”
Section: Introductionmentioning
confidence: 68%